Characterization of a novel cometabolic degradation carbazole pathway by a phenol-cultivated Arthrobacter sp. W1. (October 2015) - Shi, Shengnan; Qu, Yuanyuan; Zhou, Hao; Ma, Qiao; Ma, Fang
Highlights: Cometabolic degradation CA by phenol-grown W1 was firstly studied. Structural properties of 3, 4-dihydroxycarbazole were identified for the first time. A novel mode of CA hydroxylation by monooxygenases was clarified. A series of novel indole derivatives were identified as the metabolites. A novel CA catabolism pathway employed by W1 was reliably constructed. Abstract: Arthrobacter sp. W1 was used to characterize the pathways involved in cometabolic degradation of carbazole (CA) with phenol as the primary substrate. To clarify the upper pathway of cometabolic degradation CA, Escherichia coli strain BL21 expressing phenol hydroxylase from strain W1 (PHIND ) was investigated to degrade CA. Firstly, CA was initially monohydroxylated at C-2 and C-4 positions to produce 2- and 4-hydroxycarbazole, followed by successively hydroxylated to the corresponding 1, 2- and 3, 4-dihydroxycarbazole, of which 3, 4-dihydroxycarbazole was unequivocally identified for the first time. To characterize the downstream cometabolic degradation CA pathway, purified 3, 4-dihydroxycarbazole was used as the substrate for phenol-grown W1, and a series of novel indole derivatives were identified. These results suggested that a novel pathway of CA catabolism was employed by strain W1 via a successive hydroxylation and meta -cleavage pathway. These findings provide new insights into the cometabolic degradation CA process and have potential applications in biotechnology and bioremediation.